2005
DOI: 10.3201/eid1108.041367
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Foodborne Gastroenteritis, Australia

Abstract: An estimated 4.0–6.9 million episodes of foodborne gastroenteritis occur in Australia each year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
161
7
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 19 publications
14
161
7
5
Order By: Relevance
“…The evidence for the impact of zoonotic disease on human health is very strong, partly as a result of the aforementioned Global Disease Burden studies: of the 35 leading communicable causes of death, 15 are either zoonoses or have a zoonotic component. There have also been a number of systematic studies showing the high burden of foodborne diseases, the majority of which are zoonoses (Adak et al 2005;CDC 2005;Hall et al 2005). Unfortunately, none of the most important diseases have been thoroughly investigated in the context of developing countries.…”
Section: The Role Of Livestock In Pro-poor Development Processesmentioning
confidence: 99%
“…The evidence for the impact of zoonotic disease on human health is very strong, partly as a result of the aforementioned Global Disease Burden studies: of the 35 leading communicable causes of death, 15 are either zoonoses or have a zoonotic component. There have also been a number of systematic studies showing the high burden of foodborne diseases, the majority of which are zoonoses (Adak et al 2005;CDC 2005;Hall et al 2005). Unfortunately, none of the most important diseases have been thoroughly investigated in the context of developing countries.…”
Section: The Role Of Livestock In Pro-poor Development Processesmentioning
confidence: 99%
“…6 Transmission may occur when people come into contact with a contaminated environment or an infected animal. Some Salmonella serotypes are more commonly found in the environment and in distinct geographical areas.…”
Section: Environmental Salmonella Infectionmentioning
confidence: 99%
“…Controls were drawn (about one per case) from a control bank generated during a national crosssectional survey of gastroenteritis conducted in 2001 ; a description of the survey is given by Hall et al [31] and a description of control selection is reported by Stafford et al [13]. In brief, households were selected using random digit dialling during the gastroenteritis survey, a household member was asked to participate in the survey and subsequently consent to be part of a control bank.…”
Section: Study Basementioning
confidence: 99%